PENGEMBANGAN MODEL PELATIHAN KEWIRAUSAHAAN UNTUK PEREMPUAN PENGANGGURAN DI KABUPATEN DEMAK - Lies Indriyatni; Panca Wahyuningsih; Agus Budi Purwanto (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
In the end of this Research first aims to find entrepreneurship training model for unemployment women in Demak regency. Model can be used as a reference for implementation of the training program entrepreneurship in various institutions formal and informal programs. Also useful forprogram management entrepreneurship training.To achieve that goal, used model design, which was adopted from the model research and development (The R & D model of Plomp, 1997).This research started with the preliminary investigation research and design (first year ) activities in the or introduction to know the issues appears on the field is related to entrepreneurship training for women unemployment done so far, whether that will be done by formal and informal programs. First year research will be arranged initial design entrepreneurship training model for women unemployment and equipment and the handbook of these organizations program Implementation services for women unemployment. Next, in the final test, evaluation and revision (next year) activities in initial design entrepreneurship training developed by doing testing to get a model evaluation entrepreneurship training for women unemployment.Based on data collected from almost all respondents had followed training programs or entrepreneurial skills that comes from the state budget, but it has not been able to create new entrepreneurs. This was attributed to the organizer programs that did not include cargo supporting order entrepreneurship in the curriculum  program that they were to perform.Entrepreneurship training model that developed in this research on some parts: 1) system of selection participants, 2) material and training method, 3) apprenticeship, 4) capital management, 5) mentoring for business, 6) evaluation and a report. Training materials on technical skills resource potential in accordance with local and interest entrepreneur, andentrepreneurial order that able to grow and develop the attitude entrepreneurship. The implementation of the training entrepreneurship use methods based on the main problem based learning (PBL).